Early-career midwives' experiences of perineal assessment and repair after normal vaginal birth. (2nd January 2019) - Hunter, Caroline; Bick, Debra
Abstract : Background: It falls within the midwife's scope of practice to assess and repair first- and second-degree perineal trauma. Failure to accurately do so can lead to significant maternal morbidities. Evidence suggests that this can be a source of anxiety for midwives. Aims: To explore early-career midwives' experiences of performing perineal assessment and repair after normal vaginal birth. Methods: A qualitative semi-structured interview study analysed via interpretative phenomenological analysis. Six purposively-selected midwives, qualified for fewer than 5 years, were interviewed. Findings: The study identified two superordinate themes. 'Working and learning in an imperfect environment' highlighted inadequacies in pre-registration midwifery education in preparing midwives for suturing, and a lack of support for developing their clinical skills once qualified. 'Knowing myself, understanding my women', highlighted midwives' understanding of suturing in terms of professional identity, responsibility for women's wellbeing and promotion of continuity. Conclusions: Midwives often experience their pre-registration training as poor preparation for suturing in practice. Once qualified, preceptorship programmes can be variable and support for skills development is often lacking. Time constraints and structural hierarchies can inhibit the ability of midwives to articulate and advance their learning needs.